ISLAMIC ECONOMIC LEGAL REVIEW TOWARDS GOLD TRADING BY THE BROKERS IN “PASAR 45 MANADO” - Adriandi Kasim (Tasharruf: Journal Economics and Business of Islam, 2020)
Using a qualitative method with a sociological-normative approach, it was found that most of the gold brokers in Pasar 45 Manado were not honest in the practice of gold trading transactions between brokers and sellers, if the broker found a seller who wanted to sell their gold are compromising, then the dishonest broker will take advantage which is not reasonable or contrary to Islamic principle. For example: manipulating the weight of the gold which are going to sell, because the gold is suspected to not belong to the seller, or because the seller at that time is in dire need of money, or even the gold is the result of stealing, so in this case not a few gold brokers in Pasar 45 Manado market deal with the law because of being caught in a case of fraud. Thus the implications in this study are 1. For gold brokers in the 45 Manado market area, in order to follow the rules of law and Islamic law that have been determined in the Koran so that no party is harmed and every fortune obtained gets blessings from Allah. 2. For gold brokers in the area of Pasar 45, in making transactions they must pay attention to the conditions of the goods to be sold so that they do not harm other people and themselves. 3. For religious leaders in order that constantly give an understanding to the people of Manado City about how to trade in accordance with Islamic principles.